Implementing exposure limits for players in contact team sports: review of principles and practices - Colin W. Fuller (Frontiers in Sports and Active Living)
Concerns have been raised that professional athletes taking part in contact team sports, such as football and rugby union, are subject to the risk of post-career adverse health conditions. These health concerns include neurodegenerative diseases resulting from head impacts and osteoarthritis in lower limb joints due to wear and tear. There have been suggestions that athletes in contact team sports should be subject to exposure limitations to mitigate these risks. At the present time, little information or guidance is available for athletes and sport governing bodies about how such limitations should be identified and implemented. The criteria used for defining occupational health concerns and the role and nature of occupational exposure limits are discussed. Consideration is given to whether these criteria have been considered and embraced in research studies examining adverse health conditions in professional sport. Recommendations are presented for how future research studies investigating post-career, sport-related, adverse health concerns should be planned and implemented in order to provide the occupational health information required to make evidenced-based decisions about potential health concerns in professional sport.